2016
DOI: 10.1007/s00792-016-0859-1
|View full text |Cite
|
Sign up to set email alerts
|

HU histone-like DNA-binding protein from Thermus thermophilus: structural and evolutionary analyses

Abstract: The histone-like DNA-binding proteins (HU) serve as model molecules for protein thermostability studies, as they function in different bacteria that grow in a wide range of temperatures and show sequence diversity under a common fold. In this work, we report the cloning of the hutth gene from Thermus thermophilus, the purification and crystallization of the recombinant HUTth protein, as well as its X-ray structure determination at 1.7 Å. Detailed structural and thermodynamic analyses were performed towards the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…Thus, we believe that the exhibited dynamic equilibrium between monomer and dimeric states of Hup aided by conformational flexibility of their DNA binding C‐terminal arms provides a level of exquisite control to regulate rapid and accurate functioning of cell cycle activities or modulating gene expression in response to changing external conditions . The HU are ubiquitously found in bacteria that grow in a wide range of temperature (cold to hot) conditions and temperature‐induced structural changes, especially in DNA binding proteins, may play a role in modulating gene expression crucial for their survival under varying temperature conditions. The temperature dependent studies revealed that Hup exhibits dynamic equilibrium between its M‐ and D‐conformations (Figure ), and this equilibrium shifts more towards M–conformation at near physiological temperature.…”
Section: Functional Relevance Of the Studymentioning
confidence: 99%
“…Thus, we believe that the exhibited dynamic equilibrium between monomer and dimeric states of Hup aided by conformational flexibility of their DNA binding C‐terminal arms provides a level of exquisite control to regulate rapid and accurate functioning of cell cycle activities or modulating gene expression in response to changing external conditions . The HU are ubiquitously found in bacteria that grow in a wide range of temperature (cold to hot) conditions and temperature‐induced structural changes, especially in DNA binding proteins, may play a role in modulating gene expression crucial for their survival under varying temperature conditions. The temperature dependent studies revealed that Hup exhibits dynamic equilibrium between its M‐ and D‐conformations (Figure ), and this equilibrium shifts more towards M–conformation at near physiological temperature.…”
Section: Functional Relevance Of the Studymentioning
confidence: 99%
“…The protein expression of the two proteins and their purification were carried out following the method of Papageorgiou et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…For the overproduction of CaWRKY40-GFP, the pET-11a-CaWRKY40-GFP plasmid was used to transform the Escherichia coli expression strain BL21(DE3). The protein expression of the two proteins and their purification were carried out following the method of Papageorgiou et al (2016).…”
Section: Overproduction and Purification Of The Recombinant Cawrky40-gfpmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar with pathogenic Nocardia, Mycobacterium smegmatis can survive for long periods during persistent infections and escape from the intracellular killing of phagocytes, and a class of histone-like DNA-binding proteins (HLPs), the mycobacterial DNA-binding protein 1 (MDP1), were revealed to involved in this progress (Enany et al, 2017). HLPs are basic bacterial proteins, which are analogues to eukaryotic histones (Li, Arnold-Schulz-Gahmen, & Kellenberger, 1999;Papageorgiou et al, 2016;Ravinder & Goyal, 2017). The function of HLPs is associated with the nucleoid, and they play important roles in the maintenance of DNA architecture, such as DNA replication, recombination and transcription (Anuchin, Goncharenko, Demidenok, & Kaprelyants, 2011).…”
mentioning
confidence: 99%